Microglia after Seizures and in Epilepsy - Toshimitsu Hiragi (Cells, 2018)
Microglia are the resident immune cells in the brain that constitute the brain’s innate immune system. Recent studies have revealed various functions of microglia in the development and maintenance of the central nervous system (CNS) in both health and disease. However, the role of microglia in epilepsy remains largely undiscovered, partly because of the complex phenotypes of activated microglia. Activated microglia likely exert different effects on brain function depending on the phase of epileptogenesis. In this review, we mainly focus on the animal models of temporal lobe epilepsy (TLE) and discuss the proepileptic and antiepileptic roles of activated microglia in the epileptic brain. Specifically, we focus on the roles of microglia in the production of inflammatory cytokines, regulation of neurogenesis, and surveillance of the surrounding environment in epilepsy.